Observation of excited Ω0c baryons in Ω−b→Ξ+cK−π− decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; et al. (Physical review, 2021)
The first observation of the Ω−b→Ξ+cK−π− decay is reported using p p collision data at center of mass energies of 7, 8, and 13 TeV collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. Four excited Ω0c baryons are observed in the Ξ+c K− mass projection of the Ω−b→Ξ+cK−π− decays with the significance of each exceeding five standard deviations. They coincide with the states previously observed in prompt pp and e+e− production. Relative production rates, masses, and natural widths of the states are measured, and a test of spin hypotheses is performed. Moreover, the branching ratio of Ω−b→Ξ+cK−π− is measured relative to the Ω−b→Ω0cπ− decay mode and a precise measurement of the Ω−b mass of 6044.3±1.2±1.1+0.19−0.22 MeV is obtained.